Muslim young consumer intention to purchase halal cosmetic and personal care products / Zulaiha Ahmad ... [et al.] - Ahmad, Zulaiha; Azizan, Farah Lina; Kassim, Shamshul Anaz; Ibrahim, Ima Ilyani; Zailani, Muhammad Amirul Afiq (Universiti Teknologi MARA, Kedah, 2024)
The trend in choosing Halal cosmetics and personal care products is still very low among Muslim society, especially among the younger generations. Most of them purchase particularly more on Halal food products rather than Halal cosmetic and personal care products. Young Muslim population is still not aware of “Halal” concept when purchasing and use cosmetic and personal care products. Therefore, this paper aims to provide improved understanding of the influential factors towards the intention to purchase Halal cosmetic and personal care products among the younger generation. Data were collected from 303 young Muslim consumers in northern state, Malaysia. They were selected using stratified random sampling. A set of self-administered questionnaires with five interval Likert scales was used. The study employed a quantitative research method to examine all hypothesis. A multiple regression analysis was used to examine Halal certificate, product characteristics, social influence and attitude which are the determinant factors of intention to purchase Halal cosmetic and personal care products. The findings showed that only Halal certificate, products characteristics and attitude have significantly influenced the intention to use Halal cosmetic and personal care products. Meanwhile, social influence does not significantly influence intention to purchase the products. This study contributes to Halal cosmetic studies by illustrating how the young generation choose and use Halal cosmetic and personal care products.